The intervention of rehabilitation nurse in promoting efficient decannulation of critically ill patients: scoping review protocol - Correia, Ana Sofia Castro (2023)
Introduction: Prolonged mechanical ventilation is associated with difficult ventilatory weaning and considered an indication for tracheostomy in intensive care. The presence of a tracheostomy, despite facilitating ventilator weaning, may originate other complications for the patient, so decannulation should be performed as soon as possible. Must, also, have an interdisciplinary approach and the rehabilitation nurse can play a leading role. Objective: To map the available evidence on the intervention of rehabilitation in decannulation of critically ill patients. Methods: This scoping review will follow the PCC strategy and the PRISMA® recommendations by JBI®. We intend to answer the question: “What is the intervention of the specialist nurse in rehabilitation for efficient decannulation in tracheostomized patients, in intensive care?”. The search will be performed in MEDLINE, CINAHL® Complete, Cochrane Database of Systematic Reviews, MedicLatina, Nursing & Allied Health Collection, Scopus®, Web of Science, ProQuest, RCAPP, OpenGrey, MedNar and Google Scholar databases. Two independent reviewers will evaluate the studies obtained, analyzing their titles, abstracts, and afterwards, full text, using a third reviewer if there are discrepancies. Conclusion: It is expected that this review will provide information for the creation of a protocol, which guides the decision making of rehabilitation nursing in decannulation.